Carga do câncer de mama na Grande Cuiabá, Mato Grosso, Brasil - Oliveira, Jânia Cristiane de Souza (2021)
Breast cancer is the most incident in the female population. Worldwide, represents the fifth leading cause of death in females. Objective: to analyze the burden of breast cancer in women living in Great Cuiaba, Mato Grosso, and the specific objectives were met in manuscripts. First specific objective: to analyze the trend of completeness and consistency of cancer records in the database of the Hospital Registry of Cancer (Registro Hospitalar de Câncer – RHC, em portugês) of Mato Grosso. Second specific objective: to analyze the trend of the standardized rate of incidence and mortality due to breast cancer in women in Great Cuiaba. Brazil, 2000 to 20016. Third specific objective: to analyze the specific ten-year survival of women with breast cancer in the 2008 and 2009 cohort, from the population base of Great Cuiaba, Mato Grosso, Midwest region of Brazil. Fourth specific objective: to analyze the overall and specific survival in 5 years for female breast cancer, from the population base of Great Cuiaba. Mato Grosso, Brazil. Methods: the study consisted of four manuscripts with quantitative, ecological and non-concurrent cohort design. Data sources: all cancer records of the RHC of Mato Grosso, from 2008 to 2014; population-based cancer registry (Registro de câncer de base populacional – RCBP, em português) and mortality information system (Sistema de informação de mortalidade – SIM, em português). The period analyzed from RCBP e SIM databases varied according to the study. For the other manuscript, women with a cytopathological or histopathological diagnosis of breast cancer or who died from this pathology, living in Great Cuiaba, were eligible. For manuscript two, the dependent variable was composed of breast cancer incidence and mortality rates in Great Cuiaba, Capital and Várzea Grande. Period from 2000 to 2016, for all ages and by age group <50 years old and ≥50 years old. The annual percent change and the average annual percent change were calculated. 11 for the survival study, the dependent variable was the time from the breast cancer diagnosis to death from any cause - overall survival (sobrevida global, em português SG) and specific cause of death from breast cancer - specific survival (sobrevida específica, em português, SE), period from 2008 to 2009 (manuscript 3) and from 2008 to 2013 (manuscript 4). Manuscript 3 included only deaths from breast cancer, without presence of censorship and was used parametric analysis (Weibull model and log-Weibull regression). Manuscript 4 included failures and censorship and analysis of the SG and SE was done by the method Kaplan-Meyer and log-rank test, regression model for Cox proportional risks, computing hazard ratios (RH). Results: Study 1: the variables that presented the highest incompleteness were tumor-lymphnode-metastasis, schooling, status at the end of the first treatment and occupation. Study 2: both incidence and mortality showed an increasing trend in all four-year periods analyzed , for Grande Cuiaba and Capital, with the highest rates in the age group of 50 years-old or more. Study 3: the mean time to death from breast cancer was approximately 51.1 months. Worse 10 years SE was observed for women aged ≥50 years-old and for white race/color. Study 4: in SG, women with 70 years-old or more had worse survival. In the SG and SE, women with low schooling and without a partner had a lower survival than the other. Final considerations: the study reinforces breast cancer as a challenge for the public health in Great Cuiaba. It also reinforces the need for continuing education for greater completeness of RCBP and RHC databases.